Comparative study on effects of volume-controlled ventilation and pressure-limited ventilation for neonatal respiratory distress syndrome - Jae Jin Kim; Mun Jung Hwang; Sang Geel Lee (Korean Pediatric Society, 2010)
Purpose:In contrast with traditional time-cycled, pressure-limited ventilation, during volume-controlled ventilation, a nearly constant tidal volume is delivered with reducing volutrauma and the episodes of hypoxemia. The aim of this study was to compare the efficacy of pressure-regulated, volume controlled ventilation (PRVC) to Synchronized intermittent mandatory ventilation (SIMV) in VLBW infants with respiratory distress syndrome (RDS). Methods : 34 very low birth weight (VLBW) infants who had RDS were randomized to receive either PRVC or SIMV with surfactant administration : PRVC group (n=14) and SIMV group (n=20). We compared peak inspiratory pressure (PIP), duration of mechanical ventilation, and complications associated with ventilation, respectively with medical records. Results:There were no statistical differences in clinical characteristics between the groups. After surfactant administration, PIP was significantly lower during PRVC ventilation for 48hrs and accumulatevive value of decreased PIP was higher during PRVC ventilation for 24hrs (P<0.05). Duration of ventilation and incidence of complications was no significant difference. Conclusion:PRVC is the mode in which the smallest level of PIP required to deliver the preset tidal volume in VLBW infants with RDS, adaptively responding to compliance change in lung after surfactant replacement.